OPTIMALISASI RETRIBUSI DAERAH DARI SEWA RUMAH DINAS DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PADA BADAN PENGELELOLA KEUANGAN DAN ASET DAERAH KABUPATEN SIKKA - Yohanes Yuaniku; Maria Silvana Mariabel Carcia; Margaretha Yulianti (Jurnal Projemen UNIPA, 2026)
This study aimed to analyze efforts to optimize official residence rental retribution as one of the sources of Local Own-Source Revenue (PAD) in Sikka Regency. The main problem identified was the accumulation of official residence rental arrears due to the low awareness of Civil Servants (ASN) in fulfilling their payment obligations. The method used was qualitative, with data collection techniques conducted through observations and interviews during the internship program. The results of the study showed that the Regional Financial and Asset Management Agency (BPKAD) had implemented various strategic measures, such as mapping priority areas in six sub-districts, standardizing rental values through an appraisal team, and implementing a non-cash payment system through Bank NTT based on Sikka Regent Regulation No. 22 of 2024. However, strengthening law enforcement and the digitalization of asset management still need to be improved to minimize arrears